Mass production of metal-doped graphene from the agriculture waste of Quercus ilex leaves for supercapacitors: inclusive DFT study. Issue 18 (15th March 2021) - Tatrari, Gaurav; Tewari, Chetna; Karakoti, Manoj; Pathak, Mayank; Jangra, Ritu; Santhibhushan, Boddepalli; Mahendia, Suman; Sahoo, Nanda Gopal
Abstract : This work reports a facile, eco-friendly, and cost-effective mass-scale synthesis of metal-doped graphene sheets (MDGs) using agriculture waste of Quercus ilex leaves for supercapacitor applications. Abstract : This work reports a facile, eco-friendly, and cost-effective mass-scale synthesis of metal-doped graphene sheets (MDGs) using agriculture waste of Quercus ilex leaves for supercapacitor applications. A single step-degradation catalyst-based pyrolysis route was used for the manufacture of MDGs. Obtained MDGs were further evaluated via advanced spectroscopy and microscopic techniques including Raman spectroscopy, FT-IR, XRD, SEM/EDX, and TEM imaging. The Raman spectrum showed D and G bands at 1300 cm −1 and 1590 cm −1, respectively, followed by a 2D band at 2770 cm −1, which confirmed the synthesis of few-layered MDGs. The SEM/EDX data confirmed the presence of 6.15%, 3.17%, and 2.36% of potassium, calcium and magnesium in the obtained MDGs, respectively. Additionally, the FT-IR, XRD, TEM, and SEM data including the plot profile diagrams confirmed the synthesis of MDGs. Further, a computational study was performed for the structural validation of MDGs using Gaussian 09. The density functional theory (DFT) results showed a chemisorption/decoration pattern of doping for metal ions on the few-layered graphene nanosheets, rather than a substitutional pattern. Further, resulting MDGs were used as an active material for the fabrication of a supercapacitor electrode using the polymer gel of PVA–H3 PO4 as the electrolyte. The fabricated device showed a decent specific capacitance of 18.2 F g −1 at a scan rate of 5 mV s −1 with a power density of 1000 W kg −1 at 5 A g −1 .